2015
DOI: 10.4081/aiua.2015.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Internal urethrotomy versus plasmakinetic energy for surgical treatment of urethral stricture

Abstract: We believe that plasmakinetic surgery is better method than the cold knife technique for the treatment of urethral stricture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…At the 12-month follow-up, Cecen [ 29 ] and Ozcan [ 30 ] considered that patients who did not complain of voiding difficulties and had a maximum urine flow rate > 12 mL/s were considered free from recurrence. On the other hand, Atak [ 9 ] and Jhanwar [ 24 ] considered patients without voiding complaints and a maximum urine flow rate > 10 mL/s as not having recurrence after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…At the 12-month follow-up, Cecen [ 29 ] and Ozcan [ 30 ] considered that patients who did not complain of voiding difficulties and had a maximum urine flow rate > 12 mL/s were considered free from recurrence. On the other hand, Atak [ 9 ] and Jhanwar [ 24 ] considered patients without voiding complaints and a maximum urine flow rate > 10 mL/s as not having recurrence after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In their studies, Cecen et al, [ 25 ] and Ozcan et al, [ 26 ] found that the intervention successes in the absence of any voiding difficulties and with the Q-max greater than 12 mL/s. However, other studies reported an effective operation with Q-max greater than 10 mL/s in patients without voiding difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Another type of energy for IU is plasmakinetic. There are several studies in the literature about the treatment of urethral strictures with plasma kinetics [ 25 , 26 ]. Until now, there is no clear criterion to assess success or failure after IU.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] and Ozcan at al. [ 26 ] deemed the intervention successful in their studies when the patient did not complain of any voiding difficulty and the Qmax was >12 mL/s. Other studies were accepted as successful if the patient did not report any voiding difficulty, and the Qmax was greater than 10 mL/sec [ 5 , 9 ].…”
Section: Discussionmentioning
confidence: 99%